Adjustment Problems dan Psychological Well-Being pada Siswa Akseleran (Studi Korelasional pada SMPN 19 Jakarta dan SMP Labschool Kebayoran Baru) - Priscillia Susan Misero; Lydia Freyani Hawadi (Jurnal Psikologi: PITUTUR, 2012)
Owned by a gifted student akseleran, as intellectually gifted students,taking them to the demands of external and internal demands. A student akseleran must adapt themselves to these demands. However, it is not easy.There are a number of problems they face because of it. Noted there are six main problems of adjustment (adjustment problems) students akseleran ie, school assignments are not challenging, poor interpersonal relationships, parental expectations, perfectionism, multipotensialitas, and high involvement (Chan, 2006). Those problems are a source of stress for students and psychological conditions may interfere with his well-being.This is certainly not beneficial because it can cause the student can not perform optimally. This study seeks to prove whether there is a relationship between adjustment problems and psychological well-being in students akseleran .. In addition, this study also attempted to figure out what adjustment the most significant problems associated with psychological well-being.Melalui a correlational study in SMP and SMP 19 Jakarta Labschool Kebayoran Baru, found a significant negative relationshipbetween psychological adjustment problems with the well-being thestudents akseleran. In addition, problems of adjustment dimensionsperfectionism is a problem that has the most significant relationship with psychological well-being.